(5x – 5 ) – ( 3x – 3)
Question
Updated 9/5/2014 4:11:57 AM
This conversation has been flagged as incorrect.
Edited by andrewpallarca [9/5/2014 4:09:26 AM], Flagged by andrewpallarca [9/5/2014 4:09:28 AM]
g
Original conversation
User: (5x – 5 ) – ( 3x – 3)

Weegy: is equal to 8x
beboythewizkid|Points 2048|

User: (8x – 2) + (7x + 6)

User: (4x – 3.5) – (3x + 1.7)

Weegy: First, get rid of the parenthese, 4x-3.5-3x-1.7 Second, Subtraction, x-5.2. x-5.2x is the answer.
Boyinbedroom|Points 249|

User: (12y3 + 9 y2 + 21y) ÷ 3y

Weegy: x+3y=-15 3y=-x-15 y=(-1/3)x-5
user1583|Points 1061|

Question
Updated 9/5/2014 4:11:57 AM
This conversation has been flagged as incorrect.
Edited by andrewpallarca [9/5/2014 4:09:26 AM], Flagged by andrewpallarca [9/5/2014 4:09:28 AM]
Rating
8
(5x – 5 ) – ( 3x – 3)
= (5x - 5) + (-3x + 3)
= 2x - 2
8
(8x – 2) + (7x + 6) = 15x + 4
8
(4x – 3.5) – (3x + 1.7)
= (4x - 3.5) + (-3x - 1.7)
= x - 5.2
8
(12y^3 + 9y^2 + 21y) ÷ (3y)
= (12y^3/3y) + (9y^2/3y) + (21y/3y)
= 4y^2 + 3y + 7

Questions asked by the same visitor
(12y3 + 9 y2 + 21y)
Weegy: x+3y=-15 3y=-x-15 y=(-1/3)x-5 User: (10x2 – 14x – 12) ÷ (5x + 3) Weegy: x=2 User: (4x + 1 )(x2 – 9x + 5) Weegy: Best Answer - Chosen by Voters ((4/x) - (2/4x)) / ((1/2x) + (3/2x)) = ((16/4x) - (2/4x))/(4/2x) = (14/4x)/(2/x) = (14/4x) * (x/2) = 14x/8x = 14/8 = 7/4 (More)
Question
Updated 6/4/2014 8:21:17 AM
12y^3 + 9 y^2 + 21y = 3y(4y^2 + 3y + 7)
Confirmed by andrewpallarca [9/5/2014 4:12:40 AM]
(10x^2 – 14x – 12) ÷ (5x + 3)
= (5x + 3)(2x - 4)/(5x + 3)
= 2x - 4
Confirmed by andrewpallarca [9/5/2014 4:13:07 AM]
5x+2x^2+8x+34+8x+12x=
Question
Updated 7/16/2014 2:02:29 AM
5x+2x^2+8x+34+8x+12x=2x^2+33x+34
Confirmed by andrewpallarca [7/16/2014 4:18:12 AM]
(5x^2 + 3x ) + ( 2x + 5)
Weegy: First, get rid of the parentheses. 5x^2+3x+2x+5. Second, addition. 5x^2+5x+5 Third, divide everything by 5. x^2+x+5 User: (5x – 5 ) – ( 3x – 3) Weegy: please indicate what you would like to solve for or how you would like to solve this, you did not give enough information for me to do anything (More)
Question
Updated 9/18/2016 2:46:08 PM
(5x^2 + 3x ) + ( 2x + 5)
= 5x^2 + 5x + 5
(5x – 5 ) – ( 3x – 3)
= (5x - 5) + (-3x + 3)
= 2x - 2
33,785,745
*
Get answers from Weegy and a team of really smart live experts.
Popular Conversations
Which is not a factor of ...
Fill in the blank. One of the best reasons to write is to _______ ...
Weegy: One of the best reasons to write is to express what we think. Planning is the first stage of the writing ...
name the eight parts of speech. Defined the word grammar. In what ...
Weegy: Power is the time rate at which work is done or energy is transferred.
Wikipedia pages should get high ratings for all user intents because ...
Weegy: Wikipedia pages should get high ratings for all user intents because information is always helpful. FALSE. ...
National Preparedness Mission?
Weegy: Preparedness refers to a very concrete research-based set of actions that are taken as precautionary measures in ...
S
L
Points 163 [Total 163] Ratings 0 Comments 163 Invitations 0 Online
S
L
P
R
Points 94 [Total 2240] Ratings 0 Comments 94 Invitations 0 Offline
S
Points 94 [Total 94] Ratings 7 Comments 4 Invitations 2 Online
S
L
P
P
L
P
Points 86 [Total 6416] Ratings 0 Comments 86 Invitations 0 Offline
S
L
P
Points 76 [Total 1834] Ratings 0 Comments 76 Invitations 0 Offline
S
L
Points 56 [Total 255] Ratings 0 Comments 16 Invitations 4 Offline
S
L
Points 48 [Total 364] Ratings 3 Comments 18 Invitations 0 Offline
S
L
1
1
1
1
1
1
1
1
1
1
1
1
1
1
1
1
Points 48 [Total 3770] Ratings 4 Comments 8 Invitations 0 Offline
S
R
L
P
P
Points 47 [Total 3278] Ratings 0 Comments 47 Invitations 0 Offline
S
Points 40 [Total 50] Ratings 4 Comments 0 Invitations 0 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.